2016
DOI: 10.5385/nm.2016.23.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Deaths in the Neonatal Intensive Care Unit between 2002 and 2014

Abstract: Purpose: To report the causes and patterns of death among infants admitted to our neonatal intensive care unit (NICU) over a 13-year period. In addition, we analyzed trends regarding the type of end-of-life care provided. Results: Of the 5,223 admissions to our NICU, 97 neonates died. The overall mortality rate was 1.9%. The most common cause of death was sepsis (15%). At a lower gestational age, infants died of extreme prematurity and complications of prematurity. Among term infants, the principal cause of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Research within the Korean NICU suggested that 65–73% of death cases received excessive intensive care, including resuscitation, supporting this claim. 20 21 The current law proclaims the patients’ right to make treatment decisions and their right to dignity. However, decision-making based on ethical considerations remain challenging owing to the restriction of discontinuing LST only during the death-imminent stages of terminal illness.…”
Section: Discussionmentioning
confidence: 99%
“…Research within the Korean NICU suggested that 65–73% of death cases received excessive intensive care, including resuscitation, supporting this claim. 20 21 The current law proclaims the patients’ right to make treatment decisions and their right to dignity. However, decision-making based on ethical considerations remain challenging owing to the restriction of discontinuing LST only during the death-imminent stages of terminal illness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented the worldwide increment rates of EOLD made in neonatal intensive care units (NICUs) over the past years (Chan et al, 2016; Kim et al, 2018; Michel et al, 2018; Park and Kim, 2016). Rates of EOLDs made at newborns’ EOL were reported to be around 34% in NICUs in Latin America (Fajardo et al, 2012), 54% in Hong Kong (Chan et al, 2016), 63% in the United Kingdom (Aladangady et al, 2017), and between 71% and 81% in Canada (Hellmann et al, 2016; Lam et al, 2016).…”
Section: Introductionmentioning
confidence: 99%